Strategic Interaction among Heterogeneous Price-Setters in an Estimated DSGE Model - Coibion, Olivier; Gorodnichenko, Yuriy (The Review of Economics and Statistics, 2011)
We consider a dynamic stochastic general equilibrium model (DSGE) in which firms follow one of four price‐setting regimes: sticky prices, sticky information, rule of thumb, or full‐information flexible prices. The parameters of the model, including the fraction of each type of firm, are estimated by matching the moments of the observed variables of the model to those found in the data. We find that sticky price firms and sticky information firms jointly account for over 80% of firms in the model. We compare the performance of our hybrid model to pure sticky price and sticky information models along various dimensions, including monetary policy implications.